Work-Life Balance in Relation to Workload Experience and Work-Life Programme: A Study in a Government Ministry of Malaysia (Journal of Business Management and Accounting, 2015)
This  study  focused  on  the  work-life  balance  and  gender  which  was  tested  using  t-test; and work-life balance in relation to workload experience at workplace, and work-life programme valued as important among staff at Ministry of Youth and Sports in Putrajaya, both of which were  measured  using  Pearson  correlation.  The  findings  indicated  that  staff  at  the  Ministry experienced a balance in their work-life, regardless of gender,while having intermediate level of  workload  at  the  workplace.  The  relationship  between  workload  and  work-life  balance among  staff  was  negatively  correlated.  Although  work-life  balance  was  reported   at  a satisfying  level,  none  of  the  work-life  programmes  valued by  the  employees  were  associated significantly  with  work-life  balance  experienced  by them.  Nevertheless,  there  is  hope  that programmes valued by staff as important to them and capable of reducing workload levels are applicable  for  future  considerationby  respective  parties  in  implementing  policies  related  to the work-life programme.